Sosialisasi dan Edukasi Protokol Kesehatan Covid-19 Berbasis Masyarakat: Peningkatan Kapasitas SIBAT PMI Kecamatan Sukajadi, Kota Bandung - Ruhanda, Ruhanda; Rachman, Fitriana Sidikah; Sriwati, Sriwati (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2022)
The government has declared the Covid-19 pandemic a national disaster. Since then, various regulations related to preventing the spread of Covid-19 have been issued. The government's policy must be followed by the whole community. Policy socialization can be adopted more quickly with community participation. First, by participating in implementing the policy and second, participating in disseminating the policy. PMI as a national humanitarian institution also plays a role. Through PMI's SIBAT Team, government policies can be disseminated to the public. The PKM team then helped train the SIBAT team in order to increase their capacity and assist in the implementation of community-based outreach programs. After training and mentoring, there is a program of activities held in the context of socializing and educating health protocols, especially for school children, carried out by the SIBAT team where PKM is carried out.